Applications of GIS and Remote Sensing in Soil Environment Monitoring - Ganga, Antonio; Repe, Blaž; Elia, Mario (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint focuses on environmental monitoring as a key issue in the sustainable management of land resources, where the increasing availability of temporal and spatial soil data plays a fundamental role. Remote sensing and GIS (Geographic Information System) applications allow the efficient handling of these data with the aim of developing predictive and robust models to reduce land degradation and soil erosion.